Control strategy and experimental analysis of a direct-expansion solar-assisted heat pump water heater with R134a - Kong, Xiangqiang; Jiang, Kailin; Dong, Shandong; Li, Ying; Li, Jianbo (Energy (Oxford), 2018)
A direct-expansion solar-assisted heat pump (DX-SAHP) system was designed and built in Qingdao China, which was used to supply domestic hot water. The system mainly consisted of a bare solar collector/evaporator with area of 1.56 m2, a rotary-type hermetic compressor with rated power of 400 W, an electronic expansion valve (EEV) and a micro-channel aluminum flat tube condenser with single surface area of 0.435 m2 surrounding a 0.195 m3 water tank. The system was charged with 800 g of R134a. Based on the degree of superheat at the outlet of the solar collector/evaporator, a control strategy for the system was developed and tested over a wide range of operating conditions, which proved that it could regulate the degree of superheat in range of 5–10 °C effectively. Then the thermal performance of the system was experimentally studied under various operating conditions. Experimental results showed that for most of the time in 2016, when the 0.195 m3 water was heated to the temperature between 55 °C and 60 °C, the coefficient of performance (COP) of the prototype device was higher than 3.0. As the solar radiation intensity or ambient temperature increased, the COP of the system increased, and the heating time decreased. •A direct-expansion solar-assisted heat pump system was designed and built.•A control strategy was developed and tested under different operating conditions.•The presented control strategy was based on the degree of superheat.•The system thermal performance was experimentally studied.